Tumor-targeted IL-12 combined with local irradiation leads to systemic tumor control via abscopal effects in vivo. (3rd June 2017) - Eckert, Franziska; Jelas, Ivan; Oehme, Moritz; Huber, Stephan M.; Sonntag, Katja; Welker, Christian; Gillies, Stephen D.; Strittmatter, Wolfgang; Zips, Daniel; Handgretinger, Rupert; Schilbach, Karin
ABSTRACT: NHS-IL12 is an immunocytokine, a fusion protein of IL12's functional domains and a necrosis-targeting antibody, which has shown significant effects against human rhabdomyosarcoma xenografts in a humanized tumor model, including terminal growth arrest and differentiation of the tumor cells. Here, we locally irradiated the tumors, increasing necrosis and consequently intratumoral immune cytokine availability, and asked whether this effect may surmount efficacy of single treatment modality. Humanized mice bearing bilateral rhabdomyosarcoma xenografts were evaluated for tumor burden and survival after irradiation, systemic NHS-IL12 therapy or a combination of both. Intratumoral immune compartments were characterized by immunohistochemistry and molecular methods. TH 1-cytokine dependency of underlying effector mechanisms were investigated in vitro in several human tumor cell lines. NHS-IL12 when combined with irradiation terminally arrested tumor growth and significantly improved survival. Combination treatment induced dense intratumoral T-cell infiltrates, clonal epitope-specific T-cell expansions, expression of cytotoxins, decreased pro-tumorigenic cytokines and induced senescence and differentiation in the cancer cells. Senescence and differentiation were reproduced in vitro and confirmed to be dependent on TH 1 cytokines IFNγ and TNF-α. NHS-IL12 and irradiation together induced broad intratumoral TH 1 biased NK and T-cell compartments, established antitumoral cytokine profiles and irreversibly growth arrested tumor cells, leading to systemic cancer control and improved survival. For the first time, we describe immune-induced senescence as a novel mechanism resulting from a treatment regimen combining irradiation with immunotherapy.